A Lexile-Based Analysis of Adaptive Reading Intervention Efficacy Across Proficiency Tiers in Chinese EFL Learners - Sun, Miaomiao; Hui, Jiaojiao (Journal of Educational Research and Policies, 2025)
This study examines the impact of integrating the Achieve 3000 (A3000) platform into the English major curriculum to bridge the gap between students’ reading proficiency and the text difficulty levels of required course materials and the Test for English Majors-Band 4 (TEM4). Using a longitudinal action research design with 203 Chinese first-year English majors of different reading proficiency tiers, the study assessed reading growth within Lexile framework over one academic year. Results revealed a mean gain of 135L, while 47.1% of students reached Textbook 2 level yet only 1.9% of students reached TEM4 readiness (1171L), indicating persistent reading proficiency gaps despite improvement. Proficiency-stratified analysis showed differential effects: mid-tier learners (601–900L) exhibited the strongest progress after the reading intervention, while foundational learners (≤600L) demonstrated limited advancement and advanced learners (≥901L) displayed plateaued growth, suggesting the need for differentiated interventions—remedial support for lower-proficiency students and enriched challenges for advanced learners. The findings underscore A3000’s efficacy in mid-proficiency ranges but highlight the necessity for tailored strategies to address varying learner needs.